2014
DOI: 10.11604/pamj.2014.19.255.4745
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practices towards rabies and determinants of dog rabies vaccination in households: a cross sectional study in an area with high dog bite incidents in Kakamega County, Kenya, 2013

Abstract: IntroductionAn estimated 55,000 people die from rabies annually. Factors promoting dog vaccination, estimates of vaccination coverage and knowledge on rabies are important for effective rabies control. We sought to establish these estimates at household (HH) level and whether rabies knowledge is associated with proper control practices.MethodsCross-sectional cluster survey with two-stage sampling was employed in Kakamega County to enroll HH members above 18 years. A set of questions related to rabies knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
20
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 8 publications
9
20
1
1
Order By: Relevance
“…Respondents who did not have any family exposure to dog bite were higher to have poor practice than having exposure history. This is consistent with the study done in Kakamega, Kenya and Hawasa [17,18,24].This implies having exposure history helps to have good practice towards rabies prevention and control. But everybody need to aware of prevention both before and after bite exposure.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Respondents who did not have any family exposure to dog bite were higher to have poor practice than having exposure history. This is consistent with the study done in Kakamega, Kenya and Hawasa [17,18,24].This implies having exposure history helps to have good practice towards rabies prevention and control. But everybody need to aware of prevention both before and after bite exposure.…”
Section: Discussionsupporting
confidence: 90%
“…A double proportion formula was used to calculate sample size by applying Epi info stat calc version 7. The following assumptions were considered in calculating sample size: 95% confidence interval, 80% power, 1:1 ratio of exposed to non-exposed group, OR of 2.7 and taking the proportion of P1=81.1% of urban households and P2=92.1% of rural households and multiplied by 1.5 of design effect and added 10% of non-response rate and then became 558 participants [17] (Table1).…”
Section: Sample Size and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2015 surveillance publication reported that the rate of rabies in biting dogs was 7%; however, at the time of this report the community bite rate was not known [9]. This survey reports an annual bite rate of 0·9% (a comparable figure to what has been reported in other developing countries) [1013]. The annual bite rate was highest in the 18–29 years age group and declined with each following age group (Table 4).…”
Section: Discussionmentioning
confidence: 62%